Body art and performance: the body as language - Vergine, Lea; Vergine, Lea (Skira, 2007)
When The Body as Language ("Body-art" and Performance) appeared in 1974, it was immediately a huge publishing hit, reviewed by some of the most influential art historians and writers (Giulio C. Argan, Edoardo Sanguineti, Max Kozloff, Lucy Lippard, François Pluchart, Peter Gorsen, Evelyn Weiss and many others). A direct testimony of the birth and development of one of the most controversial art trends, Lea Vergine's book avails of a series of texts by the artists themselves, whom the author had asked to contribute with a statement about the illustrations of their work. Featuring a thorough documentation of original photographs and film photograms, videotapes, happenings, actions and performances, the book analyses the evolution of this phenomenon through the works of sixty artists, including Gina Pane, Gilbert & George, Urs Lüthi and Katharina Sieverding, Rebecca Horn, Trisha Brown, Günter Brus and many others who have worked with and on the body. In an absolutely unusual publishing event, nearly thirty years after the first edition, the text--by now a classic--is republished with all the original photographic material. The volume is enhanced and brought up-to-date by an afterword by Lea Vergine, who observes the changes of Body Art throughout the nineties: Orlan, Stelarc, Ron Athey, Franko B., Yasumasa Morimura, Jana Sterbak, Matthew Barney are "virtuosos of disorder and hungry for afflictions of any and every kind, mystics--like persons who display the subjection of their bodies to cruel and invasive devices, or who revel in virtual fantasies of such self-inflicted pains--destroy themselves in order newly to find themselves. . . . They finally pay a visit to the world of the saints and victims, exploring and prolonging its seductions.
Keywords: art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; performance; premier cycle; thématiques

Sex objects: art and the dialectics of desire - Doyle, Jennifer (University of Minnesota Press, 2006)
The declaration that a work of art is “about sex” is often announced to the public as a scandal after which there is nothing else to say about the work or the artist-controversy concludes a conversation when instead it should begin a new one. Moving beyond debates about pornography and censorship, Jennifer Doyle shows us that sex in art is as diverse as sex in everyday life: exciting, ordinary, emotional, traumatic, embarrassing, funny, even profoundly boring. Sex Objects examines the reception and frequent misunderstanding of highly sexualized images, words, and performances. In chapters on the “boring parts” of Moby-Dick, the scandals that dogged the painter Thomas Eakins, the role of women in Andy Warhol's Factory films, “bad sex” and Tracey Emin's crudely evocative line drawings, and L.A. artist Vaginal Davis's pornographic parodies of Vanessa Beecroft's performances, Sex Objects challenges simplistic readings of sexualized art and instead investigates what such works can tell us about the nature of desire. In Sex Objects, Doyle offers a creative and original exploration of how and where art and sex connect, arguing that to proclaim a piece of art “about sex” reveals surprisingly little about the work, the artist, or the spectator. Deftly interweaving anecdotal and personal writing with critical, feminist, and queer theory, she reimagines the relationship between sex and art in order to better understand how the two meet-and why it matters.
Keywords: approches et analyses; art contemporain; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; premier cycle; queer; sexualité; thématiques

Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

« Your Body is a Battleground » De quelques objets de l'histoire de l'art - Mader, Rachel; Schweizer, Nicole (Nouvelles Questions Féministes, 2005)
Notre article s'articule autour des points suivants: comment la critique féministe de histoire de l'art a-t-elle déplacé le ou les «objets» autour desquels s'articulait traditionnellement la discipline? Quels nouveaux «objets» ont dès lors été constitués? Et comment, à l'épreuve de ceux-ci, les histoires de l'art féministes doivent-elles, elles aussi, constamment se repositionner? L'exemple paradigmatique du corps dans la performance des années 70 nous permet d'interroger dans un deuxième temps la façon dont les artistes elles-mêmes ont déplacé la définition de l'objet, et par conséquent aussi celle du sujet - de l'œuvre comme de la perception.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; artistes féministes; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; performance; premier cycle; périodes historiques; représentation des femme*; ressource en ligne; sex2283; sexisme; systèmes d'oppressions; thématiques

Le corps de l'artiste - Warr, Tracey; Jones, Amelia; Warr, Tracey; Jones, Amelia (Phaidon, 2005)
Au cours du XXe siècle, de nombreux artistes ont utilisé leur corps à la fois comme sujet et comme objet de leur oeuvre. Le corps est présenté dans tous les états possibles et l'artiste vit littéralement son art que ce soit dans le cadre de performances, ou dans l'intimité, avec la photographie et la vidéo. Ouvrage conçu par T. Warr.
Keywords: 1900-1999; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; thématiques

Caught in the act: an anthology of performance art by Canadian women - Mars, Tanya; Householder, Johanna; Mars, Tanya; Householder, Johanna (YYZ Books, 2004)
This indispensable anthology gives readers access to an important and under-recognized subject in recent Canadian art history. Edited by two seminal Canadian performance artists, this book focuses on the 70s and 80s; a time when women made a big and noisy impact. Full of sass and insight, this essential collection is part survey, part critical discourse, and part reference book, containing five critical essays, thirty-four artist's profiles, and an extensive bibliography.
Keywords: 1900-1999; 1970-1979; 1980-1989; amériques; art contemporain; arts; canada; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques

X-elles: le sexe par les femmes - Millet, Catherine..; Leydier, Richard 19.... (Art Press, 2004)
"Adresses Internet p. 112-113."Contient : Editorial : un raz de marée, par Catherine Millet et Richard Leydier, p. 5-7. Chapitre 1 : Elles débarquent! : L'acte pour l'art, par Louis-José Lestocart, p. 10-14 ; Bandes de femmes, par Bernard Joubert, p. 15-21 ; Éros féminin surréel, par Victoria Combalía, p. 22-27 ; Ellen von Unwerth. Naughty Girls!, interview par Richard Leydier, p. 28-31 ; Organes et orgasmes. Sur quelques chanteuses sexy, par Stéphane Pencréac'h, Stéphane Ruiz et Richard Leydier, p. 32-36; Dans le train fantôme de Catherine Breillat, témoignages recueillis par Brigitte Ollier, p. 37-40 ; Clarisse Hahn. La sexualité dans le tissu de la vie, interview par Catherine Millet et Louis-José Lestocart, p. 41-44 ; Portfolio #1 : Aude du Pasquier-Grall, Sonia Koumskoff-Raissi, Nicole Tran Ba Vang, Ornela Vorpsi, Friedl Kubelka, Anne Dion., p. 45-50. Chapitre 2 : Un autre porno : Angela, Loulou et les autres ... Quand les femmes prennent la caméra, par Stéphane Ruiz, p. 52-60 ; Monika Treut. Female Misbehavior, par Thibaut de Ruyter, p. 61-65 ; Maria Beatty. De la surface à la profondeur, par Catherine Corringer, p. 66-70 ; Shu Lea Cheang. Un genre en soi, Interview par Louis-José Lestocart, p. 71-74 ; Il y a une vie après le X : Brigitte, Tabatha, Ilona et Traci, par Laurent Goumarre, p. 75-80 ; Ovidie, plus librement, interview par Laurent Goumarre, p. 81-84 ; Portfolio #2 : Kiki Seror, Virginie Boursette, Béatrice Cussol, Bettina Rheims, Pascale Lafay, Diana Michener, p. 85-90. Chapitre 3 : Autoportraits : Lamia Ziadé. "Je suis une vraie petite femme d'intérieur", interview par Brigitte Ollier, p. 92-96 ; Chloë des Lysses. Une femme en danger, interview par Richard Leydier, p. 97-101 ; Madeleine Berkhemer. Élastique, érotique, par Alix Rozès, p. 102-105 ; Elke Krystufek. Le miroir qui met à nu, interview par Joerg Bader, p. 106-109 ; La pornographie, to remember, par Judith Brouste, p. 110-111 ; Les femmes sur le Web, par Chloë des Lysses, p. 112-113.
Keywords: 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; europe; france; har4600; histoire de l'art; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques

Veil: veiling, representation, and contemporary art - Tawadros, Gilane; Bailey, David A. (MIT Press ; IVA, 2003)
No single item of clothing has had greater influence on Western images of Middle Eastern and North African women than the veil. The fascination of Western writers, artists, and photographers with the veil reflects the voyeuristic nature of our interest in what is strange and "other." Veil, which accompanies an exhibition organized by the Institute of International Visual Arts in London, explores the representation of the veil in contemporary visual arts. Providing a context for the commissioned essays are a number of classical historical texts crossing religions, cultures, genders, and ages--from Greek myths to articles published in the aftermath of September 11, 2001. Some of the contemporary artists and scholars write autobiographically about the meaning of the veil in their lives. Others take a more political approach, discussing, for example, how the events of September 11 changed the use and reception of veil imagery throughout the world. Still others take a historical approach, examining how nineteenth-century technological developments in travel and photography led to photographic depictions of both the veiled and unveiled body in relation to landscape. A number of essays look at the art historical precedents for the current interest in artwork addressing the veil, while others examine how codes of modesty and gender segregation have affected the making and viewing of films in postrevolutionary Iran. The essays are by Jananne Al-Ani, David A. Bailey, Alison Donnell, Ghazel, Salah Hassan, Reina Lewis, Hamid Naficy, Zineb Sedira, and Gilane Tawadros. The artists represented include Faisal Abdu'Allah, Kourosh Adim, Ghada Amer, Jananne Al-Ani, Farah Bajull, Samta Benyahia, Gaëtan de Clérambault, Marc Garanger, Shadafarin Ghadirian, Group AES, Emily Jacir, Ramesh Kalkur, Shirin Neshat, Harold Offeh, Gillo Pontecorvo, Zineb Sedira, Mitra Tabrizian, and Elin Strand.
Keywords: afrique; afrique du nord; approches et analyses; arts; corps; cours; discipline; féminisme islamique; har4610; histoire de l'art; mode; moyen-orient; point de vue situé; premier cycle; régions géographiques; thématiques; vêtements

Women artists: femmes artistes du XXe et du XXIe siècle - Grosenick, Uta; Fruhtrunk, Wolf (Taschen, 2001)
À l'appui de nombreuses illustrations et textes informatifs, ce livre se veut une introduction à la vie et à l'oeuvre de 46 femmes artistes contemporaines, qui ont marqué l'art du 20e siècle d'une empreinte durable, et qui influenceront encore l'art du 21e siècle. Tous les courants et tendances sont présentés : peinture, dessin, sculpture, photographie, cinéma, vidéo et Internet, installations, travail sur la nature ou le corps.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; arts; corps; cours; discipline; environnement; femmes* artistes; har4600; histoire de l'art; premier cycle; périodes historiques; thématiques

Corps, sexe et art: dimension symbolique - Pearl, Lydie (Nouvelles études anthropologiques, 2001)
Les années 60 marquent le début d'un art éphémère dans lequel l'objet d'art disparaît au profit d'une mise en scène du corps. Les Actionnistes viennois mêlent des corps féminins ou masculins dans la boue, du sang et des organes animaux etc. Comment ce qui peut paraître aberration ou perturbation de la personnalité est souvent une mise en scène microcosmique des idéologies ou des réalités politiques d'une époque : images d'une coupure Est/Ouest, de frontières infranchissables à l'époque de la guerre froide ou, au contraire, effacement des frontières au temps de la mondialisation avec des artistes de la Scène internationales
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; anthropologie; approches et analyses; art contemporain; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexualité; thématiques